The Impact of Inmate and Prison Characteristics on Prisoner Victimization. (January 2017) - Steiner, Benjamin; Ellison, Jared M.; Butler, H. Daniel; Cain, Calli M.
A considerable amount of research has been directed at understanding the sources of inmate misconduct (offending within prison), whereas few studies have focused on identifying the causes and correlates of prisoner victimization. The sources of inmate victimization should be distinguished from those of offending, however, because the policy implications of each focus differ to some extent. In order to determine the predictors of inmate victimization and stimulate further research on the topic, we systematically reviewed studies of the causes/correlates of prisoner victimization published between 1980 and 2014. Our findings revealed that predictor variables reflecting inmates' background characteristics (e.g., history of victimization), their institutional routines and experiences (e.g., history of misconduct), and prison characteristics (e.g., population size) all influence victimization.